Effects of water deficit at different stages on growth and ear quality of waxy maize - Huang, Chao; Qin, Anzhen; Gao, Yang; Ma, Shoutian; Liu, Zugui; Zhao, Ben; Ning, Dongfeng; Zhang, Kai; Gong, Wenjun; Sun, Mengqiang; Liu, Zhandong (Frontiers in Plant Science, 2023)
Summer rainfall was more, but rainfall was more concentrated, so periodic water deficit occurs from time to time. In order to study the changes of plant growth, ear yield and grain quality of waxy maize under water deficit at different growth stages, water deficit experiments were carried out under rain shelter in 2019 and 2020. Water deficit treatments were carried out at the V6-VT (DV6-VT), VT-R1 (DVT-R1) and R1-R3 (DR1-R3) stages of waxy maize, with non-water deficit as the control. The results showed that water deficit at V6-VT, the plant height and leaf area index of waxy maize decreased, the content of malondialdehyde in leaves increased, the activities of superoxide dismutase and peroxidase decreased, and the contents of soluble protein, soluble sugar and proline in leaves increased, resulted in a decrease in gas exchange parameters in leaves and an increase in leaf water. As a result, waxy maize ear length, grain number per ear, 100-grain weight fell, and fresh ear yield of DV6-VT and DVT-R1 decreased by 20.3% and 14.2% (P<0.05), respectively, and grain quality suffered as well. Total protein, starch, and lysine content in grains increased, but soluble sugar content in grains declined. Principal component analysis revealed that when water deficit occurred in waxy maize, it was the first to alter maize physiology, and then affecting ear characteristics and yield, and resulted in grain quality changes. In conclusion, water deficits at V6-VT waxy maize were the most severe, followed by VT-R1 and R1-R3.